Comparative Analysis of Cash and Debit Payment Systems for Fraud Prevention at CV. Wiratech Jaya Mandiri, Makassar Branch - Intan, Intan Timur; Rahmawati, Rahmawati (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
This study aims to analyze the comparison between cash and debit payment systems in preventing fraud at CV. Wiratech Jaya Mandiri, Makassar Branch. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that the cash payment system poses a high risk of fraud, such as embezzlement, data manipulation, and a weak audit trail due to manual recording. Conversely, the debit payment system is more effective in preventing fraud because transactions are automatically recorded in the banking system, are easily audited, and reduce physical contact with cash. This study emphasizes the importance of non-cash payments as an integral part of more accountable and efficient corporate financial governance.